Monitoring COVID-19 Impacts on Households in Sudan : Results from a Panel Household High-Frequency Phone Survey - Osman, Eiman (World Bank, Washington, DC, 2022)
This brief focuses on the household survey component of the High-Frequency Phone Survey of Households (HFS). The sampling methodology adopted for the implementation of the household survey is probabilistic, and the sampling frame is provided by a compilation of a list of phone numbers collected during the implementation of various projects/surveys during the last few years at the household level across the country. The sample is representative of the 18 states of Sudan. This brief summarizes the main results of the core questions in the completed six rounds of the Sudan HFS of the same households (i.e., a panel survey). Results of the firm survey will be reported in a separate report.